2005
DOI: 10.1016/j.jtcvs.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxic ventilation exacerbates lung reperfusion injury

Abstract: Ventilating lungs with 100% fraction of inspired oxygen at the time of reperfusion could increase the risk of lung reperfusion injury at the time of transplantation. Thus the patient should be ventilated with as low a fraction of inspired oxygen as possible to achieve adequate oxygen saturations during this critical reperfusion period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary definition of grade 3 PGD at 48 or 72 hours after transplant was associated with a relative risk (RR) of 4.8 (95% CI, 3.3-7.0; P , 0.001) for death within 90 days of transplant compared with those without grade 3 PGD and an ARI of 18% (95% CI, 12-24). Grade 3 PGD was associated with a significantly increased 1-year mortality (RR, 3.0; 95% CI, 2.3-3.9; P , 0.001) compared with those without grade 3 PGD, and an ARI of 23% (95% CI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Although the magnitude of the association between grade 3 PGD and mortality was attenuated when the alternate definition of any grade 3 PGD within 72 hours was used in the sensitivity analyses, the association remained significant at 90 days (RR, 3.5; 95% CI, 2.3-5.1; P , 0.001) and 1 year (RR, 2.5; 95% CI, 1.9-3.3; P , 0.001) (see Table E6).…”
Section: Resultsmentioning
confidence: 99%
“…Cold ischemia of the allograft followed by reperfusion results in a significant oxidative burst (26), which may overwhelm cellular antioxidant pathways and lead to cellular necrosis and apoptosis, production of proinflammatory cytokines, and worsening edema and gas exchange in animal models (27). Although we attempted to determine the FI O 2 for each subject before allograft reperfusion, we appreciate that FI O 2 is a dynamic variable, which may have been confounded by patient needs during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has shown that hyperoxic ventilation exacerbates lung reperfusion injury, suggesting that the lowest possible tension of inspired oxygen should be used during reperfusion. 14 These studies suggest that controlled ventilation or perfusion is beneficial after lung ischemia. To date, no study has investigated ventilation and perfusion applied in combination during a post-transplantation reperfusion model.…”
mentioning
confidence: 99%
“…At the time of reperfusion there is a generation of free radicals partially due to the buildup of xanthine and the conversion of xanthine reductase to xanthine oxidase. This production of toxic metabolites, potentially exacerbated by hyperoxic oxygen delivery, leads to lung inflammation and IR injury [19]. IR injury is then thought to occur in a two hit process, with donor macrophages initiating the early injury and initiating the early inflammatory cascade, followed by the recruitment of recipient neutrophils and lymphocytes [20,21].…”
Section: Discussionmentioning
confidence: 99%